Understanding public perceptions and motivations around bear part use: A study in northern Laos of attitudes of Chinese tourists and Lao PDR nationals. (November 2016) - Davis, Elizabeth Oneita; O'Connor, David; Crudge, Brian; Carignan, Annemarie; Glikman, Jenny Anne; Browne-Nuñez, Christine; Hunt, Matt
Abstract: The trade in bear bile and other bear parts in Southeast Asia and China is a leading driver in the decline of Asian bear populations, and is a serious conservation challenge. Currently consumption of bear parts is unsustainable, and could lead to the extinction of some bear species in the wild. Reducing demand for such products is at the core of strategies to conserve species involved in illegal wildlife trade. A better understanding of the attitudinal, cultural and economic mechanisms behind bear bile consumption behaviors would inform more effective education and awareness efforts towards changing these socioeconomic variables. Using surveys, we conducted a preliminary investigation in northern Laos of Chinese tourists in Laos ( n = 401) and Lao ( n = 887) respondents' use of bear bile and bear parts, as well as differences in attitudes, value orientations, and knowledge between these two groups. Our results indicate that the availability of the product leads to greater reliance, as seen in our survey results of the Chinese respondents. Lao respondents, though less reliant, were more likely to prefer wild bear bile. Chinese tourists appeared to be more knowledgeable about bear conservation, versus Lao respondents. In general, we note substantial differences in attitudes, behaviors, and knowledge of bear part consumption between Lao and Chinese respondents. Based on these results, we advise the integration of educational programs with other strategies throughout Southeast Asia to increase understanding of the linkage between the decline in bear populations and the use of bear bile and other bear parts, thereby reducing demand. Highlights: Bear bile use varies significantly between the Chinese and Lao sampled. The Chinese sampled are more empathetic towards bears and nature as a whole. The Chinese are more knowledgeable about bear conservation issues. The Lao sampled are more likely to prefer wild bile. Conservation in Asia should stress the relation of bear decline and bear bile use.